The effects of translating the Multidimensional Sexuality Questionnaire from English to Mandarin: A test of reliability and validity - Tao, Peng; Coates, Rosemary; Zhao, Yun; Maycock, Bruce (CSIRO Publishing, 2012)
Background: In China, sexuality studies using validated psychosexual instruments are limited, with no valid Mandarin language version of a sexuality inventory with psychometric properties available for use. Thus, the Mandarin version of the Multidimensional Sexuality Questionnaire (M-MSQ), comprising four subscales, originating from the Multidimensional Sexuality Questionnaire, was tested for its psychometric properties. Methods: A convenience sampling technique was employed to recruit 200 oil workers (100 males and 100 females) in northern China. Originally, 158 participants (84 males and 74 females) completed the questionnaire; these accounted for 79% of the total study sample. From this group, a subsample of 50 participants (25 males and 25 females) was randomly selected to investigate the test–retest reliability. Of these, the responses of 33 participants (18 males and 15 females) were valid. The analysis on reliability was based on Cronbach’s α, Pearson’s correlation coefficient (r) and the intraclass correlation coefficient, also including evaluation on criterion validity and discriminatory validity. Results: The M-MSQ was found to be homogeneous in factor structure, comparing well with the original questionnaire. Both the discriminatory validity and the criterion-related validity were satisfactory in the total sample and gender groups, in addition, the overall reliability of the M-MSQ was sound in internal consistency with Cronbach’s α = 0.900–0.931. The results of the test–retest showed that the stability of the M-MSQ achieved a positive statistically significant standard assessed by Pearson’s coefficient and the intraclass correlation coefficient. Conclusion: The M-MSQ is reliable in these four subscales, and may be used as a measure of sexual esteem, sexual conscious, sexual motivation and sexual satisfaction in Mandarin speakers.